New World Health Organization guidance helps protect breastfeeding as a human right. Issue 4 (10th August 2017) - Grummer‐Strawn, Laurence M.; Zehner, Elizabeth; Stahlhofer, Marcus; Lutter, Chessa; Clark, David; Sterken, Elisabeth; Harutyunyan, Susanna; Ransom, Elizabeth I.; ,
Abstract: Written by the WHO/UNICEF NetCode author group, the comment focuses on the need to protect families from promotion of breast‐milk substitutes and highlights new WHO Guidance on Ending Inappropriate Promotion of Foods for Infants and Young Children. The World Health Assembly welcomed this Guidance in 2016 and has called on all countries to adopt and implement the Guidance recommendations. NetCode, the Network for Global Monitoring and Support for Implementation of the International Code of Marketing of Breast‐milk Substitutes and Subsequent Relevant World Health Assembly Resolutions, is led by the World Health Organization and the United Nations Children's Fund. NetCode members include the International Baby Food Action Network, World Alliance for Breastfeeding Action, Helen Keller International, Save the Children, and the WHO Collaborating Center at Metropol University. The comment frames the issue as a human rights issue for women and children, as articulated by a statement from the United Nations Office of the High Commissioner for Human Rights.